The never-ending story from pluripotency to plant developmental plasticity - Gaillochet, Christophe; Lohmann, Jan U. (Development, 2015)
Plants are sessile organisms, some of which can live for over a thousand years. Unlike most animals, plants employ a post-embryonic mode of development driven by the continuous activity of pluripotent stem cells. Consequently, plants are able to initiate new organs over extended periods of time, and many species can readily replace lost body structures by de novo organogenesis. Classical studies have also shown that plant tissues have a remarkable capacity to undergo de-differentiation and proliferation in vitro, highlighting the fact that plant cell fate is highly plastic. This suggests that the mechanisms regulating fate transitions must be continuously active in most plant cells and that the control of cellular pluripotency lies at the core of diverse developmental programs. Here, we review how pluripotency is established in plant stem cell systems, how it is maintained during development and growth and re-initiated during regeneration, and how these mechanisms eventually contribute to the amazing developmental plasticity of plants.